Aberrant driving behaviors by tourists: a study of drivers in China. (October 2020) - Luo, Ling; Shi, Jing
Highlights: A new DBQ is developed to obtain the characteristics of tourists' aberrant driving behavior(ADB) A four-factor structure is extracted from tourists' ADBs by factor analysis Tourists' ADBs have different characteristics from ADBs in daily travel Attitude has significant impact on tourists' ADBs rather than attributes and skills Abstract: The motivation of this research is to understand tourists' aberrant driving behaviors while traveling by car and explore the factors related to these behaviors. A questionnaire that measures driving behaviors, driving attitudes, driving skills, and personal attributes was implemented via the Internet. Through factor analysis, a four-factor structure of tourists' aberrant driving behaviors was obtained. The result indicates that tourists' unsafe driving behaviors have different characteristics from unsafe driving behaviors in daily travel, with a higher frequency of behaviors related to environment, carelessness and fatigue driving. The main cause of these behaviors is drivers' attitude rather than skill and personal attribute. When drivers reported themselves good at staying focused, behaviors subject to "Carelessness" were found to increase as there is a more approving attitude towards careless driving among those drivers.